2006
DOI: 10.1177/154405910608501003
|View full text |Cite
|
Sign up to set email alerts
|

The Prx1 Homeobox Gene is Critical for Molar Tooth Morphogenesis

Abstract: The paired-related homeobox genes, Prx1 and Prx2, encode transcription factors critical for orofacial development. Prx1 -/-/Prx2 -/-neonates have mandibular hypoplasia and malformed mandibular incisors. Although the mandibular incisor phenotype has been briefly described (ten Berge et al., 1998(ten Berge et al., , 2001Lu et al., 1999), very little is known about the role of Prx proteins during tooth morphogenesis. Since the posterior mandibular region was relatively normal, we examined molar tooth development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
1
21
1
1
Order By: Relevance
“…These results were unexpected, as previous loss-of-function genetic mouse model studies have demonstrated the indispensable roles of these molecules [Satokata and Maas, 1994;Peters et al, 1998;D'Souza et al, 1999;Shibaguchi et al, 2003;Mitchell et al, 2006;Mitsiadis et al, 2008;Denaxa et al, 2009] in regulating early tooth development. Expression of these genes may peak during bud stage and start to decline beyond cap stage, which may explain why we saw no change in their expression levels between FDMCs (mostly bell stage) and ADMCs.…”
Section: Discussioncontrasting
confidence: 39%
“…These results were unexpected, as previous loss-of-function genetic mouse model studies have demonstrated the indispensable roles of these molecules [Satokata and Maas, 1994;Peters et al, 1998;D'Souza et al, 1999;Shibaguchi et al, 2003;Mitchell et al, 2006;Mitsiadis et al, 2008;Denaxa et al, 2009] in regulating early tooth development. Expression of these genes may peak during bud stage and start to decline beyond cap stage, which may explain why we saw no change in their expression levels between FDMCs (mostly bell stage) and ADMCs.…”
Section: Discussioncontrasting
confidence: 39%
“…For instance, two isoforms of Prx1, called Prx1A and -B, are critical for cartilage, bone, and tooth development (12)(13)(14)(15). Dlx3, -5, and -6 are transcription factors that belong to the distal-less, homeodomain-containing family of transcription factors.…”
mentioning
confidence: 99%
“…The two paired‐related homeobox genes, Prx1 and Prx2, are expressed in the mesenchyme of all teeth throughout odontogenesis (Cserjesi et al, 1992; Martin et al, 1995; ten Berge et al, 1998; Lu et al, 1999a; Mitchell et al, 2006). Although Prx1−/− and Prx2−/− mice develop normal teeth (Martin et al, 1995), when both genes are deleted dental abnormalities are observed.…”
Section: Homeobox Genes Involved In the Patterning Of The Dentition Amentioning
confidence: 99%
“…It is however unclear whether this phenotype reflects a direct function of Prx1/2 in mandibular incisor development or an indirect consequence of a shortening of the mandible. More recently, 3D reconstructions of molars from the same mice revealed that the absence of Prx1 and Prx2 results in defects in the morphology of mandibular and maxillary molars (Mitchell et al, 2006).…”
Section: Homeobox Genes Involved In the Patterning Of The Dentition Amentioning
confidence: 99%